Dental Tourism in Bangladesh: A Growing Opportunity - Iqbal, Md Ashif (Update Dental College Journal, 2023)
The concept of dental tourism, wherein individuals seek dental care abroad, has gained momentum globally. Bangladesh, with its competitive pricing, skilled dental professionals, and cultural richness, is emerging as a promising contender in this flourishing industry. This editorial explores the burgeoning trend of dental tourism in Bangladesh, emphasizing its advantages and challenges. With cost-effective treatments and a commitment to quality care, Bangladesh is poised to unlock the full potential of dental tourism, offering a unique blend of dental excellence and cultural exploration. Update Dent. Coll. j: 2023; 13(2): 1-2